THE INFLUENCE OF JOB SATISFACTION AND WORK DISCIPLINE ON THE WORK PRODUCTIVITY OF PT EMPLOYEES. PP. LONDON SUMATRA INDONESIA TBK. KENCANA SARI PALM OIL MILL LAHAT - Masdaini, Efrina (Jurnal Manajemen, 2024)
This study aims to examine the effect of job satisfaction and work discipline on employee productivity at PT PP. London Sumatra Indonesia Tbk. Kencana Sari Palm Oil Mill Lahat. This study uses associative research methods, with a population of 102 permanent employees at PT. PP. London Sumatra Indonesia Tbk. Kencana Sari Lahat. Using non-probability sampling method with accidental sampling, a sample of 81 respondents was obtained. Data collection methods include questionnaires and documentation. The data analysis technique used is multiple linear regression analysis with F test, t test, and coefficient of determination at 5% significance level. The results showed that both job satisfaction and work discipline significantly and positively affect employee productivity. The regression equation obtained is Y = 2.556 + 0.346X1 + 0.469X2, where X1 represents job satisfaction and X2 represents work discipline. The findings suggest that improving job satisfaction and implementing work discipline can improve employee work productivity.